Uso parcial de Azolla pinnata en la alimentación del camarón Penaeus vannamei desde la etapa post larva cultivado en baja salinidad - Valencia Méndez, Dayra Josselyn (2024)
The present study aimed to evaluate the use of different percentages of Azolla pinnata meal as an addition to the diet of white shrimp Penaeus vannamei at the post-larval stage, cultured at low salinity. A completely randomized design was used with 16 experimental units, 4 replications, and a total of 800 shrimp divided into four treatments: T0 (commercial feed, 0% azolla), T1 (10% azolla), T2 (20% azolla), and T3 (30% azolla). The results indicated that shrimp fed with commercial diets had higher final weights (T0: 3.107 g), significantly superior to those in T1 (1.478 g), T2 (2.603 g), and T3 (3.008 g). However, T3 showed the greatest weekly weight gain. The water parameters—pH, dissolved oxygen, conductivity, ammonia, hardness, and salinity—remained within acceptable ranges, with no significant differences between treatments. Mortality was not significantly different in weeks 1 and 4, but higher mortalities were observed in treatments with higher azolla concentrations during weeks 2 and 3. In the cost-benefit analysis, Treatment 3 (T3) showed the highest profitability, generating a return of $2.78 per dollar invested, compared to $0.87 for Treatment 0. It is concluded that Azolla pinnata meal has high organic protein potential as a partial ingredient in the diet of shrimp cultured at low salinity, without adversely affecting their development or the environment.